Molly Brown's Junior Days - Speed, Nell, 1878-1913; Wrenn, Charles L. (Charles Lewis), 1880-1952 (Salt Lake City, UT : Project Gutenberg, 2011)
"Molly Brown's Junior Days" by Nell Speed is a novel written in the early 20th century. This work is part of a series focusing on the life of a spirited protagonist named Molly Brown, following her college adventures alongside her friends at Wellington College. The narrative highlights themes of friendship, self-discovery, and the challenges of transitioning from youth to adulthood amid academic and social pressures. The opening portion of the book introduces the chaotic arrival of students back at Wellington College, particularly focusing on Nance Oldham, who finds herself overwhelmed by the tumult of settling in. As she navigates her surroundings and encounters her diverse classmates, including her friend Otoyo Sen, Nance reflects on her fondness for the college and the excitement of the new academic year. The chapter sets the stage for the dynamics of friendship among the girls and hints at forthcoming challenges, including the treatment of a brash newcomer, Minerva Higgins, whose confidence may not align with the college's established social norms. This introduction establishes a lively college atmosphere filled with humorous interactions and the promise of growth and adventure for the characters involved. (This is an automatically generated summary.)
Release date is 2011-07-12
E-text prepared by Stephen Hutcheson, Rod Crawford, Dave Morgan, eagkw, and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: College students -- Juvenile fiction; College stories; Young women -- Social life and customs -- Juvenile fiction; Tricks -- Juvenile fiction; Japanese -- United States -- Juvenile fiction; Social values -- Juvenile fiction